Investigation of spudcan–soil interaction in a sloped seabed using centrifuge model tests. Issue 3 (21st August 2018) - Kim, J.-H.; Jeong, Y.-H.; Park, H.-J.; Kim, D.-S.; Kim, S.-J.; Lee, S. W.; Chung, M.; Choi, J.; Han, J.-T.
Abstract : The installation of mobile jack-up platforms on a sloped seabed creates hazardous conditions on the spudcans and legs by inducing detrimental moment and horizontal loads that normally do not occur on a flat seabed. Despite these risks, only a limited number of studies on the effect of a sloped seabed have been reported. In this paper, a series of experiments were performed to investigate the effect of a sloped seabed on the spudcan behaviour on sand using a centrifuge. The scaled spudcan was installed on saturated silty sand at different slope angles (0, 5 and 10°) and the combined vertical, horizontal and moment loads were recorded during installation. The results clearly showed that the horizontal and moment loads increased with slope angles. In addition, the penetration behaviour of the spudcan installed on the sloped seabed was different from that on a flat seabed especially until the full width of the spudcan becomes embedded. However, horizontal and moment loads were attenuated once the full diameter was deeply embedded in the soil.